2017
DOI: 10.1136/bmjopen-2016-012633
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME): a systematic review and meta-ethnography of qualitative studies

Abstract: ObjectiveTo synthesis the qualitative studies of children's experiences of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME).DesignSystematic review and meta-ethnography.BackgroundCFS/ME is an important disabling illness, with uncertain cause and prognosis. As a result, children with CFS/ME can find themselves living with greater uncertainty and stigma, exacerbating the impact of the condition. There is a growing body of qualitative research in CFS/ME, yet there has been no attempt to systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 80 publications
4
55
0
Order By: Relevance
“…The findings support previous research which shows the negative impacts that symptoms of CFS/ME can have on a young person's life. Symptoms of CFS may mean that individuals with CFS have to miss large amounts of school, or give up valued and enjoyable activities, a consequence of which may be social isolation (Crawley & Sterne, 2009;Jelbert et al, 2010;Parslow et al, 2017). Many participants in this study reported a lack of awareness and understanding of CFS/ME by their peers, schools, healthcare professionals, and in the wider community.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The findings support previous research which shows the negative impacts that symptoms of CFS/ME can have on a young person's life. Symptoms of CFS may mean that individuals with CFS have to miss large amounts of school, or give up valued and enjoyable activities, a consequence of which may be social isolation (Crawley & Sterne, 2009;Jelbert et al, 2010;Parslow et al, 2017). Many participants in this study reported a lack of awareness and understanding of CFS/ME by their peers, schools, healthcare professionals, and in the wider community.…”
Section: Discussionmentioning
confidence: 86%
“…This finding also supports existing research in which young people with symptoms of CFS/ ME report negative impacts of symptoms such as reduction in activity, school absence and difficulties maintaining social relationships. This is in addition to the negative emotional impact of CFS/ME and difficult feelings such as loss, isolation, and loneliness that are often reported by young people with CFS/ME (Jelbert et al, 2010;Parslow et al, 2017;Taylor et al, 2016). Previous research also suggests that having an illness like CFS/ME is associated with low mood and depression as well as anxiety, but the direction of causality is unclear (Bould et al, 2013;Taylor et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to an earlier finding of no statistical evidence between depressive symptoms and low HRQoL in adolescents with CFS/ME [16], and that there is a lack of depression found in diagnostic evaluation of the patient group, it is tempting to assume that depressive symptoms may develope as result of living with CFS/ME. Adolescents with CFS/ME are not able to do the things they want to, and they suffer from loss, disruption and coping barriers [1,31,32,37]. Living with CFS/ME in adolescense require that the surroundings are aware and supportive in order to give the adolescents a potential to prevent depressive symptoms and gain hopes of an active and productive future [1].…”
Section: Discussionmentioning
confidence: 99%
“…There is now a strong body of research, especially amongst children and young people, on the biographical disruption associated with myalgic encephalomyelitis and chronic fatigue syndrome (ME/CFS) and also the development of hope for recovery (Parslow et al . ). In this study of adults, the authors focus on the experiences of those in their sample, and what it means to ‘recover’.…”
mentioning
confidence: 97%